Identification of an unusual by‐product in the industrial production of 2‐Methyl‐3‐furanthiol. (30th August 2017) - Ding, Rui; Zhang, Shishi; He, Dawei; Liu, Yongguo; Yang, Shaoxiang; Sun, Baoguo; Tian, Hongyu
Abstract: A by‐product provided by the producer of 2‐methyl‐3‐furanthiol was characterized by 1D and 2D NMR, GC–MS (EI) and HRMS analyses. It was identified to be 4‐(5‐methyl‐2‐furylthio)‐5‐methyltetrahydrofuran‐2‐thione and its precursor 2‐methyl‐5‐thioacetylfuran was also determined. 2‐Methyl‐5‐thioacetylfuran was formed by the nucleophilic addition of AcSH to the aldehyde group of 4‐oxo‐2‐pentenal during the industrial production of 2‐methyl‐3‐furanthiol. The hydrolysis of 2‐methyl‐5‐thioacetylfuran under basic conditions gave 5‐methyl‐2‐furanthiol, which underwent autothiylation to lead to the formation of 4‐(5‐methyl‐2‐furylthio)‐5‐methyltetrahydrofuran‐2‐thione. Abstract : A by‐product provided by the producer of 2‐methyl‐3‐furanthiol was characterized by 1D and 2D NMR, GC–MS (EI) and HRMS analyses. It was identified to be 4‐(5‐methyl‐2‐furylthio)‐5‐methyltetrahydrofuran‐2‐thione and its precursor 2‐methyl‐5‐thioacetylfuran was also determined. 2‐Methyl‐5‐thioacetylfuran was formed by the nucleophilic addition of AcSH to the aldehyde group of 4‐oxo‐2‐pentenal during the industrial production of 2‐methyl‐3‐furanthiol. The hydrolysis of 2‐methyl‐5‐thioacetylfuran under basic conditions gave 5‐methyl‐2‐furanthiol, which underwent autothiylation to lead to the formation of 4‐(5‐methyl‐2‐furylthio)‐5‐methyltetrahydrofuran‐2‐thione.